Progression from meiosis I to meiosis II in Xenopus oocytes requires de novo translation of the mosxe protooncogene. - Kanki, J P (1991)
The meiotic maturation of Xenopus oocytes exhibits an early requirement for expression of the mosxe protooncogene. The mosxe protein has also been shown to be a component of cytostatic factor (CSF), which is responsible for arrest at metaphase of meiosis II. In this study, we have assayed the appearance of CSF activity in oocytes induced to mature either by progesterone treatment or by overexpression of mosxe. Progesterone-stimulated oocytes did not exhibit CSF activity until 30-60 min after germinal vesicle breakdown (GVBD). Both the appearance of CSF activity and the progression from meiosis I to meiosis II were inhibited by microinjection of mosxe antisense oligonucleotides just prior to GVBD. These results demonstrate a translational requirement for mosxe, which is temporally distinct from the requirement for mosxe expression at the onset of meiotic maturation. In contrast to progesterone-treated oocytes, oocytes that were induced to mature by overexpression of mosxe exhibited CSF activity at least 3 hr prior to GVBD. Despite the early appearance of CSF, these oocytes were not arrested at meiosis I. These results indicate that, although CSF activity is capable of stabilizing maturation-promoting factor (MPF) at meiosis II and in cleaving embryos, it is incapable of stabilizing MPF prior to or at meiosis I. These studies show that the complex regulation of the cell cycle during meiosis differs significantly from the regulation of the cell cycle during mitosis.